2002
DOI: 10.1080/0954010021000096382
|View full text |Cite
|
Sign up to set email alerts
|

Features and Mode of Action of Cross-reactive Plant Allergens Relevant to Latex-fruit Syndrome

Abstract: Immediate-type reactions to articles made from natural rubber latex are collectively referred to as latex allergy. Some latex-sensitized patients also experience allergic reactions to various fruits and vegetables. This phenomenon is RESEARCH ON ALLERGENSThere have been recent surprising advancements in immunology, and we expect it to progress even more rapidly and steadily in the future using the genomic information of the human being. By contrast, research on allergenic substances (allergens) is far behind t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 112 publications
0
9
0
Order By: Relevance
“…Structural homology between putative sensitizers, to which individuals are exposed by non-oral routes, and food allergens have been documented (Ebner et al, 2001;Midoro-Horiuti et al, 2001;Yagami, 2002). These examples support the weight-of-evidence approach currently used to predict the allergenic potential of novel proteins.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Structural homology between putative sensitizers, to which individuals are exposed by non-oral routes, and food allergens have been documented (Ebner et al, 2001;Midoro-Horiuti et al, 2001;Yagami, 2002). These examples support the weight-of-evidence approach currently used to predict the allergenic potential of novel proteins.…”
Section: Discussionmentioning
confidence: 80%
“…First an individual is sensitized to the protein, and later exposure to the protein elicits a clinical allergenic response. It is clear that highly digestible proteins may elicit allergenic responses, but it has been suggested that these proteins may not be responsible for the sensitization process (Bannon et al, 2002;Viths, 1997;Yagami, 2002). For example, sensitization by cross-reactive proteins via inhalation (pollen) or dermal exposure (latex) Fig.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Class I chitinase is a representative containing a hevein-like domain. Because of this shared domain, class I chitinase is expected to be allergenic for hevein-sensitized patients [4, 5, 6]. Cross-reactivity between class I chitinase and hevein was indeed confirmed by several research groups [7, 8].…”
Section: Introductionmentioning
confidence: 81%
“…Intensive research on allergenic proteins responsible for this immediate-type hypersensitivity has revealed 13 officially registered latex allergens to date. It is notable that many of the latex allergens have something to do with the defense mechanisms of the rubber tree [2, 3, 4, 5, 6]. Defense-related proteins of higher plants are relatively conserved in the course of evolution and therefore share the partial sequences indispensable for their function.…”
Section: Introductionmentioning
confidence: 99%